Impact of the COVID-19 pandemic on anesthesia residency education - O'Brien, Jennifer; Deck, Megan; Goncin, Una; Chaya, Malone (Canadian Medical Education Journal, 2020)
The clinical role of anesthesia residents during the COVID-19 pandemic has not been well described. As qualified physicians trained in airway management, anesthesia residents could be considered essential personnel. Given the uncertain supply of protective equipment, decision-makers must consider the welfare of trainees in any decision to deploy anesthesia residents. This national survey of Canadian anesthesia residents will develop our understanding of medical education, safety, and perceptions towards training in the context of the COVID-19 pandemic. Our results may inform the Royal College of Physicians and Surgeons, program directors, and health officials in optimizing anesthesia residency training during future pandemic conditions.